PENERAPAN ADMINISTRASI DAN MANAJEMEN KEUANGAN SERTA PEMASARAN DIGITAL BAGI UMKM GARURI DI KOTA PADANG - Benni Satria; Syahyan Raesi; Neswati Neswati; Andasuryani Andasuryani; Ferry Lismanto Syaiful; Yurniwati Yurniwati (LPPM Universitas Andalas, 2022)
This activity aims to provide skills and abilities related to establishment permits, preparation of Financial Reports, and digital marketing of Garuri Micro Small And Medium Enterprises (SMEs). Garuri (Gaharu of the Republic of Indonesia is a business unit engaged in herbal tea business made from gaharu Garuri is included in the Micro, Small, and Medium Enterprises group, where MSMEs have the following problems: 1) Having a makeshift business place; 2) Unable to access funding in financial institutions; 3) Low entrepreneurial ability; 4) Low business management ability; 5) The level of general education is relatively low; 6) Lack of access to markets; 7) Access to licensing is low 8) Access to technology and information is low. Solving the problems of SMEs above is carried out in stages. The legality of a business license is one of the essential things for business actors. In addition, it is necessary to improve financial management and digital marketing ability. For that, it is necessary: (1). assistance is provided in manufacturing Business Identification Numbers for SMEs instead of SIUP for PT, and (2) financial management and digital marketing training. The methods used by the Universitas of Andalas and Assistance Team for Garuri SMEs are (1) Socialization of online and offline mentoring activities and FGDs; (2) Presentation, (3) Assistance in Data Input, and (4) Monitoring and Evaluation. Assistance in obtaining business permits (NIB) for Garuri SMEs and training in financial management and digital marketing. The results of activities are (1). MSME Garuri already has a business license, (2) assistance to MSMEs has been carried out to improve administration and financial management by filling out a business financial recording application issued by Bank Indonesia under the name SIAPIK; 3. MSME Garuri has created an account to market its products on social media.